Vogt-Koyanagi-Harada syndrome potentially associated with COVID-19 vaccination: a case report and literature review - Zhiqiang Cui; Yan Luo; Yanli Yi; Xuli Guo; Yuqi Liu; Xiang Wang; Xiaonan Liu (Immunological Medicine)
To investigate the potential association between COVID-19 vaccination and Vogt-Koyanagi-Harada (VKH) syndrome, offering novel insights for the diagnosis and management of vaccine-related ocular disorders. A case report combined with a literature review was conducted. A 19-year-old male developing VKH after receiving the second dose of an inactivated COVID-19 vaccine was analyzed. Clinical features, treatment outcomes (glucocorticoid therapy with 2-year follow-up), and literature-based comparisons were evaluated. PubMed-indexed cases of vaccine-associated VKH were systematically reviewed, and causality was assessed using the Naranjo Adverse Drug Reaction Probability Scale. The patient presented with bilateral blurred vision 14 days post-vaccination, diagnosed as VKH with retinal neuroepithelial detachment via fluorescein angiography (FFA) and optical coherence tomography (OCT). Oral prednisone (starting at 60 mg/day, tapered gradually)restored visual acuity to near-normal levels (OD: 20/40, OS: 20/33), consistent with the patient’s reported baseline vision. Within 8 weeks, with no recurrence during follow-up. Literature analysis revealed vaccine-associated VKH symptoms typically emerged at a median of 8 days post-vaccination, aligning with the WHO’s 40-day adverse event monitoring window. A Naranjo score of 4 indicated a probable vaccine-triggered immune response. COVID-19 vaccines may induce VKH via immune dysregulation mechanisms, particularly in genetically predisposed individuals. Although causality remains unconfirmed, clinicians should maintain vigilance for acute bilateral uveitis post-vaccination. Glucocorticoid therapy demonstrates efficacy in symptom resolution and relapse prevention. Enhanced active surveillance and mechanistic studies on vaccine-related ocular adverse events are warranted.